Corporate brand equilibrium: identity analysis - Jukić, Dinko (Oeconomica Jadertina, 2018)
The paper presents and analyses contemporary corporate brand models, brand personality constructs as well as model C2ITE. Equilibrium of the corporate brand is constituted by an integrated model of different theoretical approaches to brand phenomena. The primary model is acquired as hexagonal brand identity, as it is also a starting construct that unites the derived models. The corporate brand is causal and depends on joint communication with all C2ITE features. The corporate brand origin is the corporate identity displayed and interpreted by the ACID test model. Corporate identity is essential for several reasons: it enables further creation of the corporate brand, image and other constructs, but also because of the strategic dimension of brand positioning in consumer consciousness. The design of the brand personality is confirmed by the CBBE model dimensions. The corporate brand equilibrium is suggested by the diversification of identity, image and personality. The corporate brand must have the ability to react quickly to market changes, as well as developed collaborative approach to all participants.
Keywords: brand; corporate brand; corporate identity; brand personality; model C2ITE; ACID test